It can be proved that the polynomial function f ( x ) = x 4 − 6 x 3 + 1 1 x 2 − 6 x − 2 0 2 0 has two distinct real roots x 1 and x 2 and two distinct complex conjugate roots x 3 and x 4 . Find the number ( ( 2 x 1 − x 2 ) 2 + ( 2 ∣ x 3 − x 4 ∣ ) 2 ) 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We are going to make
c
=
2
0
2
0
. Then the polynomial
f
(
x
)
can be represented as
f
(
x
)
=
x
4
−
6
x
3
+
1
1
x
2
−
6
x
−
c
Now we can make
x
=
X
+
2
3
.
Then
f
(
X
+
2
3
)
=
(
X
+
2
3
)
4
−
6
(
X
+
2
3
)
3
+
1
1
(
X
+
2
3
)
2
−
6
(
X
+
2
3
)
−
c
=
X
4
−
2
5
X
2
+
1
6
9
−
c
.
Let us solve the equation
X
4
−
2
5
X
2
+
1
6
9
−
c
=
0
.
The solutions of this biquadratic equations are:
1
+
c
−
4
5
,
−
1
+
c
−
4
5
,
i
1
+
c
+
4
5
,
−
i
1
+
c
+
4
5
.
Then the roots of the polynomial
f
(
x
)
are
x
1
=
2
3
+
1
+
c
−
4
5
,
x
2
=
2
3
−
1
+
c
−
4
5
,
x
3
=
2
3
+
i
1
+
c
+
4
5
,
x
4
=
2
3
−
i
1
+
c
+
4
5
.
Therefore,
(
(
2
x
1
−
x
2
)
2
+
(
2
∣
x
3
−
x
4
∣
)
2
)
2
=
(
1
+
c
−
4
5
+
1
+
c
+
4
5
)
2
=
(
2
1
+
c
)
2
=
4
(
1
+
c
)
=
8
0
8
4
.
We might recognise the coefficients of the quartic - it can be rewritten as f ( x ) = x ( x − 1 ) ( x − 2 ) ( x − 3 ) − M
where M = 2 0 2 0 . If we replace x with x + k for some constant k , the quantity we're asked to find will not change (it's invariant under translations). Noting that x ( x − 1 ) ( x − 2 ) ( x − 3 ) is symmetric about x = 2 3 suggests putting k = 2 3 ; so let g ( x ) = f ( x + 2 3 ) = ( x + 2 3 ) ( x + 2 1 ) ( x − 2 1 ) ( x − 2 3 ) − M
This becomes g ( x ) = ( x 2 − 4 9 ) ( x 2 − 4 1 ) − M = x 4 − 2 5 x 2 + 1 6 9 − M
We'll factor this as two quadratics; one with roots x 1 , x 2 and one with roots x 3 , x 4 . Note that g ( x ) contains no odd powers of x ; the factorisation will be of the form 1 6 1 ( x 2 − p ) ( x 2 − q ) , where p + q = 2 5 and p q = 1 6 9 − M , and without loss of generality p > 0 > q .
The roots are, of course, x 1 , 2 = ± p and x 3 , 4 = ± q ; so ( ( 2 x 1 − x 2 ) 2 + ( 2 ∣ x 3 − x 4 ∣ ) 2 ) 2 = ( p − q ) 2 = ( p + q ) 2 − 4 p q = 4 2 5 − 4 9 + 4 M = 8 0 8 4
Problem Loading...
Note Loading...
Set Loading...
x 4 − 6 x 3 + 1 1 x 2 − 6 x − 2 0 2 0 x 4 − 6 x 3 + 1 1 x 2 − 6 x + 1 ( x 2 − 3 x + 1 ) 2 ⟹ x 2 − 3 x + 1 = 0 = 2 0 2 1 = 2 0 2 1 = ± 2 0 2 1
⟹ ⎩ ⎨ ⎧ x 2 − 3 x + 1 − 2 0 2 1 = 0 x 2 − 3 x + 1 + 2 0 2 1 = 0 ⟹ x = 2 3 ± 9 − 4 + 4 2 0 2 1 = 2 3 ± 5 + 4 2 0 2 1 = x 1 , x 2 ⟹ x = 2 3 ± 9 − 4 − 4 2 0 2 1 = 2 3 ± i 4 2 0 2 1 − 5 = x 3 , x 4 real roots complex roots
⟹ ( ( 2 x 1 − x 2 ) 2 + ( 2 ∣ x 3 − x 4 ∣ ) 2 ) 2 = ( 4 5 + 4 2 0 2 1 + 4 4 2 0 2 1 − 5 ) 2 = 8 0 8 4